Answer:
The complete statement is
![(R_(y-axis) \circ R_(y=x)) (2, 3) = (-3, 2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/74bxyzpmmom6bm61lub7xfs2qwz4wsvakw.png)
Explanation:
Given that we have a composition transformation where the operation R stands for reflection, we are to start from the right operation then we work on the left as follows
![(R_(y-axis) \circ R_(y=x)) (2, 3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/doniqhwvwzkxdupq1pcw175r5mcca8yfp9.png)
The reflection of a point (x, y) cross the line y = x is (y, x)
Therefore, when (2, 3) is reflected across the line y = x it becomes (3, 2)
The next operation, which is the reflection across the line y = x is then found as follows;
The reflection of a point (x, y) cross the y-axis is (-x, y)
Therefore, when (3, 2) is reflected across the y-axis it becomes (-3, 2)
Therefore, the complete statement is
![(R_(y-axis) \circ R_(y=x)) (2, 3) = (-3, 2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/74bxyzpmmom6bm61lub7xfs2qwz4wsvakw.png)